Effectiveness of Bromelain and Papain Enzymes in Hatching Media with Different Salinity on the Hatching Success of Tilapia (Oreochromis niloticus) Eggs - Fani Fariedah; Maheno Sri Widodo; Soko Nuswantoro (Department of Aquaculture, 2021)
Tilapia is euryhaline fish which is commonly cultivated in former shrimp ponds, and belongs to mouthbreeders. The purpose of this study was to determine the hatching success of Tilapia eggs outside the mother's mouth, which was carried out in the salinity medium added with bromelain and papain enzymes. The research method was factorial CRD with enzyme (factor A) and salinity (factor B), with three replications. The research was conducted at the Fish Cultivation laboratory of the Faculty of Fisheries and Marine Sciences, Brawijaya University in January-February 2020. The results showed that papain had more effect on hatchability (93.77%), while the salinity of 5 ppt was the salinity that produced the highest hatchability (93.89%). Moreover, the hatchability was also influenced by the interaction between the enzyme and salinity, namely papain enzyme with a salinity of 5 ppt (98.89%). Meanwhile, bromelain had more effect on the survival of larvae (87.86%), and the salinity that produced the highest survival rate was at 5 ppt (85.75%), but the interaction between enzyme and salinity did not have an effect on the survival of larvae.